2021
DOI: 10.1371/journal.pone.0259279
|View full text |Cite
|
Sign up to set email alerts
|

Age effects in autobiographical memory depend on the measure

Abstract: Studies examining age effects in autobiographical memory have produced inconsistent results. This study examined whether a set of typical autobiographical memory measures produced equivalent results in a single participant sample. Five memory tests (everyday memory, autobiographical memory from the past year, autobiographical memory from age 11–17, word-cued autobiographical memory, and word-list recall) were administered in a single sample of young and older adults. There was significant variance in the tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 67 publications
2
9
1
Order By: Relevance
“…These findings reveal that memory elaboration appears less influenced by the increased task demands of retrieval switching and more by the age-dependent shift from episodic to semantic retrieval. Support for this view can be found in a recent study from Mair and colleagues (Mair et al, 2021), who showed how autobiographical memory specificity, the ability of recalling unique events when the instructions required to do so, was associated with efficiency in executive abilities, whereas details production, the ability of describing the unfolding of the event, appears to be less dependent on such executive abilities.…”
Section: Effect Of Retrieval Switching On Memory Elaborationmentioning
confidence: 94%
See 1 more Smart Citation
“…These findings reveal that memory elaboration appears less influenced by the increased task demands of retrieval switching and more by the age-dependent shift from episodic to semantic retrieval. Support for this view can be found in a recent study from Mair and colleagues (Mair et al, 2021), who showed how autobiographical memory specificity, the ability of recalling unique events when the instructions required to do so, was associated with efficiency in executive abilities, whereas details production, the ability of describing the unfolding of the event, appears to be less dependent on such executive abilities.…”
Section: Effect Of Retrieval Switching On Memory Elaborationmentioning
confidence: 94%
“…The analysis of the details produced within memories provides a more detailed consideration of participants' ability to re-experience and elaborate each event (Levine et al, 2002). As these measurements, although similar, are not equally sensitive to ageing (Mair et al, 2021), we expected a different impact of task switching on our measures of interest, retrieval accuracy and detail elaboration. In particular, given that ageing is characterised by increased switching costs (for a metanalysis, see Wasylyshyn et al, 2011), we expected that switching between episodic and semantic retrieval modes would affect the performance of older adults, manifested as lower retrieval accuracy, both when comparing baseline and switching blocks, but also when comparing switch and non-switch trials.…”
Section: Current Studymentioning
confidence: 96%
“…This contrasts with episodic AM, which refers to information pertaining to a specific event that happened only once, and lasting a day or less (e.g., Last summer John and I spent the day on a beach in France; Holland et al, 2012; Levine et al, 2002; Piolino et al, 2002; Viard et al, 2007). In this article, we investigate a recurring finding in the AM literature that remains so far unexplained: older adults’ tendency to report more nonepisodic memory details, relative to young adults (Addis et al, 2008; Aizpurua & Koutstaal, 2015; Beaman et al, 2007; Devitt et al, 2016; Levine et al, 2002; Madore et al, 2014; Mair et al, 2017, 2021; Piolino et al, 2006). This study aims to distinguish between two broad potential explanations for this age difference: that nonepisodic details are a marker of cognitive decline in older adults or that they reflect a shift in communicative preferences that biases older adults toward telling an entertaining story.…”
Section: A Sign Of Cognitive Declinementioning
confidence: 99%
“…Specifically, episodic detail refers to events that are bound to a specific time and place (i.e., details concerning the who, what, when, and where); contain emotional, perceptual, and sensory details; and entail a subjective recollective experience (Fivush, 2011). Comparatively, semantic detail refers to events that occur repeatedly (e.g., attending English class) or exceed the length of one day (e.g., a trip to Australia in summer), and contain factual and general knowledge about the world (e.g., Wellington is the capital of New Zealand) and oneself (e.g., I am a high school student; Mair et al, 2021).…”
Section: Autobiographical Memory: Episodic and Semantic Detailmentioning
confidence: 99%
“…Memory specificity measures people's ability to retrieve a specific event that occurred at a particular time and place (e.g., my 21 st birthday party), compared to extended or categoric events. Episodic detail goes beyond locating an event in time and space and measures people's ability to engage in a recollective and elaborative experience (Mair et al, 2021). This is evidenced by the recall of rich contextual and emotional details (Mair et al, 2021); for example, "My best friend gave a speech at my 21 st birthday party.…”
Section: The Relationship Between Autobiographical Memory and Depressionmentioning
confidence: 99%